Fingertip Ultrasonic Array for Tactile Rendering - Rozsa, Jace; Costrell, Sarah; Martinez, Melisa Orta; Fedder, Gary K. (2024 IEEE International Conference on Robotics and Automation (ICRA), 2024)
A miniature haptic stimulation device utilizes focused ultrasound to deliver a tactile haptic sensation to the finger. The 1-3 piezocomposite device has a 1 cm 2 footprint, which is an order of magnitude smaller than other ultrasonic haptic devices and is a good candidate for wearable tactile rendering systems. The device focuses energy to a 1 mm 3 voxel. The current prototype was validated with a small, preliminary human subject study and requires an average input voltage of 68.8 V to elicit tactile sensation. The sensory drive voltage threshold will decrease with future refinement of mechanical impedance matching and focusing.